2018
DOI: 10.1111/echo.13818
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve morphology and its impact on aortic diameters—A systematic review with meta‐analysis and meta‐regression

Abstract: RL BAV phenotype is associated with larger SVD than RN BAV, and the observed differences are independent from aortic valve dysfunction degree, age, and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
3
7
0
2
Order By: Relevance
“…Additionally, the authors observed no differences in ascending aorta diameter between the BAV phenotypes,1 which is also consistent with our results 2. In our meta-analysis, we demonstrated that the aortic root diameter in BAV type I was significantly larger (on average of 1.66 mm/m 2 indexed and 2.0 mm non-indexed diameter of aorta at the level of sinus of Valsalva) in comparison to BAV type II.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the authors observed no differences in ascending aorta diameter between the BAV phenotypes,1 which is also consistent with our results 2. In our meta-analysis, we demonstrated that the aortic root diameter in BAV type I was significantly larger (on average of 1.66 mm/m 2 indexed and 2.0 mm non-indexed diameter of aorta at the level of sinus of Valsalva) in comparison to BAV type II.…”
supporting
confidence: 92%
“…Similar to the results performed recently by our team systematic review and meta-analysis of available studies on BAV morphology on aortic diameter,2 Evangelista et al presented that fusion of right and left coronary cusps (BAV type I) is related to the higher risk for dilation of proximal aorta, whereas fusion of right and non-coronary cusps (BAV type II) spares this area. Additionally, the authors observed no differences in ascending aorta diameter between the BAV phenotypes,1 which is also consistent with our results 2.…”
supporting
confidence: 85%
“…Therefore, although several haemokinetic flow characteristics related to BAV morphotype and valvular dysfunction play a role in aorta dilation phenotype, genetic predisposition cannot be ruled out, particularly since aorta dilation severity is very heterogeneous with similar conditions. Until these pending questions are answered, I agree with Miśkowiec and Kasprzak that current information established in our article and in their meta-analysis4 may impact the guidelines on the management of aortic disease, recommending that BAV-RL with root phenotype should require a close follow-up and would maybe have an earlier surgical indication. By contrast, in patients with BAV-RN, distal ascending aorta and proximal aortic arch should be assessed at diagnosis by CT or MRI, complementary to echocardiography.…”
mentioning
confidence: 78%
“…Эксцентричный трансклапанный поток крови с неодинаковой направленностью при разных фенотипах ДАК влияет как фактор, вызывающий расширение разных отделов восходящей аорты. Мета-анализ исследований, изучавших морфологию ДАК и размеры аорты, выполненный в 2018 г. D. Miskowiec и соавт., показал связь фенотипа ДАК R-L с большим размером аорты на уровне синусов Вальсальвы по сравнению с фенотипом ДАК R-N, при этом различия не зависели от степени дисфункции аортального клапана, возраста и пола [26].…”
Section: двустворчатый аортальный клапан и аортопатияunclassified